LEGAL CONSEQUENCES OF EMPLOYER NON-COMPLIANCE IN FULFILLING SOCIAL SECURITY OBLIGATIONS FOR WORKERS SUBJECTED TO UNILATERAL TERMINATION - Putri, Amelia Natalie; Gunadi, Ariawan (Jurnal Al-Dustur, 2025)
Labor social security is a fundamental right guaranteed by the state to protect workers from social and economic risks, including unilateral termination of employment. However, in practice, many employers fail to comply with their obligations to provide social security benefits to workers who have been unilaterally dismissed. This non-compliance has severe consequences for workers' well-being and legal implications for employers. This study aims to analyze the legal implications of employers' non-compliance in providing social security benefits to workers affected by unilateral termination and examine the government's role in enforcing the law and protecting affected workers. The research employs a normative juridical method with a statutory and case approach. The findings reveal that employers' failure to pay labor social security contributions can result in administrative, civil, and criminal sanctions under Law Number 24 of 2011 on BPJS and Law Number 13 of 2003 on Manpower. Additionally, workers whose rights are violated can seek legal recourse through the Industrial Relations Court (PHI). The government plays a crucial role in ensuring employer compliance through supervision, law enforcement, and providing dispute resolution mechanisms and legal assistance for workers. This study concludes that enhancing regulatory effectiveness and monitoring employer compliance is essential to safeguarding workers' rights, maintaining economic stability, and promoting social welfare in Indonesia.